A review of steel slag usage in construction industry for sustainable development - Yüksel, İsa (Springer, 2017)
Use of by-products from the steelmaking process can play an important role in achieving sustainable development. The available literature suggests that the use of iron and steel industry slags as mineral admixture or partial replacement of cement improves the microstructure of the concrete as well as its mechanical and durability characteristics. This paper reviews utilization of steel slag (SS) in the construction industry by considering current and possible future utilization fields, advantages of SS usage, and problems associated with its use. Strength and durability evolution of concretes or mortars containing SS in different ratios as aggregate or cement replacement material, combined use of ground granulated blast furnace slag with SS, and some relatively new fields of utilization of SS are also addressed. Improvements in and results of SS utilization in cement and concrete are discussed by addressing its beneficial effects. This article could help researchers to understand the recent developments in evaluation of SS in the construction industry.
Keywords: Cement; Concrete; Slag; Steel; Sustainability